Making health choices: advance care planning in aged care. Perception versus reality. Issue 1 (1st June 2011) - Sjanta, R; Jackson, L; Fullam, R; Silvester, W
Abstract : Introduction: The Making Health Choices pilot project being undertaken within Residential Aged Care Facilities in Victoria (Australia) by the Respecting Patient Choices team is currently undergoing evaluation. This presentation will provide insight into pre-existing knowledge and perceptions of advance care planning (ACP) in a group of residential aged care staff, prior to a major ACP education program. Project evaluation methods: We conducted a pre-implementation survey of staff knowledge attitudes and behaviours around ACP. Feedback from ACP debrief sessions held during the course of the education program was examined for significant themes. Results: The staff survey revealed disparities between staff perceptions of their skill and confidence in conducting ACP conversations and findings relating to the accuracy of their ACP knowledge and attitudes towards ACP. Nearly half of staff surveyed indicated they were comfortable (46%) and skilled (45%) with ACP/End-of-life discussion. However, the majority of participants reported a lack of confidence in their knowledge of key areas such as surrogate decision makers (75%) and of state laws regarding ACPs (88%). Responders performed at just above chance on a true/false test of ACP knowledge. ACP Debrief sessions reflected participants concerns about the challenging nature of ACP discussions and general ACP provision within the Australian aged care context. Discussion: The findings of the evaluation to date will be discussed in terms of ACP sustainability, future education models and in the context of systemic challenges facing the Australian Residential Aged Care.